Whole‐exome sequencing in 20,197 persons for rare variants in Alzheimer's disease - Raghavan, Neha S. (Ann Clin Transl Neurol, 2018)
OBJECTIVE: The genetic bases of Alzheimer's disease remain uncertain. An international effort to fully articulate genetic risks and protective factors is underway with the hope of identifying potential therapeutic targets and preventive strategies. The goal here was to identify and characterize the frequency and impact of rare and ultra‐rare variants in Alzheimer's disease, using whole‐exome sequencing in 20,197 individuals. METHODS: We used a gene‐based collapsing analysis of loss‐of‐function ultra‐rare variants in a case–control study design with data from the Washington Heights‐Inwood Columbia Aging Project, the Alzheimer's Disease Sequencing Project and unrelated individuals from the Institute of Genomic Medicine at Columbia University. RESULTS: We identified 19 cases carrying extremely rare SORL1 loss‐of‐function variants among a collection of 6,965 cases and a single loss‐of‐function variant among 13,252 controls (P = 2.17 × 10(−8); OR: 36.2 [95% CI: 5.8–1493.0]). Age‐at‐onset was 7 years earlier for patients with SORL1 qualifying variant compared with noncarriers. No other gene attained a study‐wide level of statistical significance, but multiple top‐ranked genes, including GRID2IP,WDR76 and GRN, were among candidates for follow‐up studies. INTERPRETATION: This study implicates ultra‐rare, loss‐of‐function variants in SORL1 as a significant genetic risk factor for Alzheimer's disease and provides a comprehensive dataset comparing the burden of rare variation in nearly all human genes in Alzheimer's disease cases and controls. This is the first investigation to establish a genome‐wide statistically significant association between multiple extremely rare loss‐of‐function variants in SORL1 and Alzheimer's disease in a large whole‐exome study of unrelated cases and controls.